Placental DNA methylation signatures of maternal smoking during pregnancy and potential impacts on fetal growth - Everson, Todd M.; Vives-Usano, Marta; Seyve, Emie; Cardenas, Andres; Lacasaña, Marina; Craig, Jeffrey M.; Lesseur, Corina; Baker, Emily R.; Fernandez-Jimenez, Nora; Heude, Barbara; Perron, Patrice; Gónzalez-Alzaga, Beatriz; et al. (Nature communications, 2021)
Maternal smoking during pregnancy (MSDP) contributes to poor birth outcomes, in part through disrupted placental functions, which may be reflected in the placental epigenome. Here we present a meta-analysis of the associations between MSDP and placental DNA methylation (DNAm) and between DNAm and birth outcomes within the Pregnancy And Childhood Epigenetics (PACE) consortium ( N = 1700, 344 with MSDP). We identify 443 CpGs that are associated with MSDP, of which 142 associated with birth outcomes, 40 associated with gene expression, and 13 CpGs are associated with all three. Only two CpGs have consistent associations from a prior meta-analysis of cord blood DNAm, demonstrating substantial tissue-specific responses to MSDP. The placental MSDP-associated CpGs are enriched for environmental response genes, growth-factor signaling, and inflammation, which play important roles in placental function. We demonstrate links between placental DNAm, MSDP and poor birth outcomes, which may better inform the mechanisms through which MSDP impacts placental function and fetal growth. Maternal smoking during pregnancy contributes to poor birth outcomes. Here the authors perform a meta-analysis of the associations between maternal smoking during pregnancy and placental DNA methylation and identify links between these and poor birth outcomes, which may better inform the mechanisms through which smoking impacts placental function and fetal growth.